Enhancing the Professional Mindset of Future Sales Professionals: Key Insights From a Master in Sales Transformation. (August 2014) - Marcos-Cuevas, Javier; Critten, Peter; Squire, Phil; Speakman, James I. F.
Sales education has grown in importance, particularly throughout the last decade, with an increasing number of university sales centers offering programs to prepare new generations of sales professionals. In this article, we describe how work-based learning, action research, and reflective practice used in a sales master program can be used in undergraduate sales education to facilitate the emergence of a new mindset of professional selling in future practitioners. This mindset is characterized by enhanced awareness and personal transformation that lead to improved relationships through the discovery of new ways of identifying and creating customer value. We argue this mindset is required to respond to the unprecedented level of change and increased complexity in professional selling. Sales education is vital to ensure that future and practicing sales professionals continuously develop the competences required to perform in demanding contexts. Universities and business schools alike now play a pivotal role in developing sales talent by combining in unique ways academic research in sales, advances in pedagogy, and practitioner experience. The findings of our study reveal the significance of student-centered pedagogies in sales curricula. We discuss how the experience gathered from educating practicing sales professionals can be applied to educating novice sales students adopting work-based pedagogies.